A large, deep 3 deg2 survey of H α, [O iii], and [O ii] emitters from LAGER: constraining luminosity functions. Issue 3 (20th January 2020) - Khostovan, A A; Malhotra, S; Rhoads, J E; Jiang, C; Wang, J; Wold, I; Zheng, Z-Y; Barrientos, L F; Coughlin, A; Harish, S; Hu, W; Infante, L; et al.
ABSTRACT: We present our measurements of the H α, [O iii ], and [O ii ] luminosity functions as part of the Lyman Alpha Galaxies at Epoch of Reionization (LAGER) survey using our samples of 1577 z = 0.47 H α-, 3933 z = 0.93 [O iii ]-, and 5367 z = 1.59 [O ii ]-selected emission line galaxies in a 3 deg 2 single, CTIO/Blanco DECam pointing of the COSMOS field. Our observations reach 5σ depths of 8.2 × 10 −18 erg s −1 cm −2 and comoving volumes of (1−7) × 10 5 Mpc 3 making our survey one of the deepest narrow-band surveys. We select our emission line galaxies via spectroscopic confirmation, photometric redshifts, and colour–colour selections. We measure the observed luminosity functions for each sample and find best fits of $φ ^\star = 10^{-3.16^{+0.09}_{-0.09}}$ Mpc −3 and $L^\star = 10^{41.72^{+0.09}_{-0.09}}$ erg s −1 for H α, $φ ^\star = 10^{-2.16^{+0.10}_{-0.12}}$ Mpc −3 and $L^\star = 10^{41.38^{+0.07}_{-0.06}}$ erg s −1 for [O iii ], and $φ ^\star = 10^{-1.97^{+0.07}_{-0.07}}$ Mpc −3 and $L^\star = 10^{41.66^{+0.03}_{-0.03}}$ erg s −1 for [O ii ], with α fixed to −1.75, −1.6, and −1.3, respectively. An excess of bright >10 42 erg s −1 [O iii ] emitters is observed and may be due to active galactic nucleus (AGN) contamination. Corrections for dust attenuation are applied assuming A Hα = 1 mag. We also design our own empirical rest-frame g − r calibration using SDSS DR12 data, test it against our z = 0.47 H α emitters with z COSMOS 1D spectra, and calibrate it for ( g − r ) between −0.8 and 1.3 mag. Dust and AGN-corrected star formation rate densities (SFRDs) are measured as log10 ρSFR /(M⊙ yr −1 Mpc −3 ) = −1.63 ± 0.04, −1.07 ± 0.06, and −0.90 ± 0.10 for H α, [O iii ], and [O ii ], respectively. We find our [O iii ] and [O ii ] samples fully trace cosmic star formation activity at their respective redshifts in comparison to multiwavelength SFRDs, while the H α sample traces ∼70 per cent of the total z = 0.47 SFRD.